(3GdebJHS aj JGQjN YdeGA GdCfOdSs - (3MjGf Hf Nda Hf MSjf Hf MjGf GdCehj HGdhdGA, CHh eQhGf,J (B469 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA GdcdGe Ydi GdNdjaI GdfGUQ dOjf Gddg s
(3BNQgG (B:s
(3jfJgi HBNQ MhGOK SfI KdGKjf hKdGKeGFI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B289 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B88s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs